2022
DOI: 10.1093/gerona/glac150
|View full text |Cite
|
Sign up to set email alerts
|

Objective Physical Activity Accumulation and Brain Volume in Older Adults: An MRI and Whole-Brain Volume Study

Abstract: A decrease in brain volume (i.e., brain atrophy) is a marker of cognitive health in older adults. Insufficient weekly accumulation of moderate and vigorous physical activity (MVPA) has been associated with lower brain volume. As this association has been established for a small number of brain areas and structures and atrophy rates seem to be nonuniform between them, more comprehensive analyses are warranted. We compared the volume of 71 brain areas and structures in 45 older adults who met and did not meet ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…As this study was the first to investigate associations between 24-hour time-use composition and grey matter volume, it is challenging to contextualize the findings with previous research. However, the findings of our correlation analyses contradict several previous studies in older adults which did report significant associations between grey matter volume and physical activity (4,6,7,11), sedentary behaviour (15) or sleep (19,20) when considered independently.…”
Section: Twenty-four-hour Time-use Composition and Grey Matter Volume...contrasting
confidence: 98%
See 3 more Smart Citations
“…As this study was the first to investigate associations between 24-hour time-use composition and grey matter volume, it is challenging to contextualize the findings with previous research. However, the findings of our correlation analyses contradict several previous studies in older adults which did report significant associations between grey matter volume and physical activity (4,6,7,11), sedentary behaviour (15) or sleep (19,20) when considered independently.…”
Section: Twenty-four-hour Time-use Composition and Grey Matter Volume...contrasting
confidence: 98%
“…On balance, a much wider range of time-use profiles were included in their study and it could be that the observed relationships between volumetric outcomes and activity levels were driven by extreme cases (e.g., highest quintiles relative to lowest) (4). Similarly, other studies that have reported associations between physical activity or sleep and grey matter volume observed differences between extreme sub-groups only (i.e., lowest VS. highest quintile of physical activity) (6,19).…”
Section: Twenty-four-hour Time-use Composition and Grey Matter Volume...mentioning
confidence: 99%
See 2 more Smart Citations
“…The guideline for daily movement behavior implies the existence of an optimal combination of movement behaviors (e.g., high LPA and MVPA, low SB, and adequate sleep; Rollo et al, 2020 ). For example, higher time spent in MVPA has been associated with greater brain volume, circulating levels of brain-derived neurotrophic factor, and synaptic plasticity ( Hillman et al, 2008 ; Neves et al, 2022 ), ultimately resulting in improved cognitive function and reduced risk of dementia ( Petermann-Rocha et al, 2021 ; Rojer et al, 2021 ). However, our results suggest that tailored physical activity promotion strategies should consider the distribution of movement behaviors in the 24 hr to achieve optimal results.…”
Section: Discussionmentioning
confidence: 99%